Modeling Work Commitment in the Covid-19 Era - Cruz García Lirios (CV. Literasi Indonesia, 2021)
In this regard, the objective of this study was modeling work commitment in the health sector. For this purpose, we used a sample of 100 social work students with experience in implementing social programs and monitoring of institutional strategies for health promotion. Were established normality, reliability, sphericity, adequation, linearity, and validity on the scale that measured labor commitment. The structural model was established in which reflective commitment to the institution was positively related to work engagement. The residual fit indices and corroborated the hypothesis of multidimensionality of work commitment.